2019
DOI: 10.1111/jcms.12841
|View full text |Cite
|
Sign up to set email alerts
|

The Trio Presidency and the Efficiency of Council Decision‐Making: An Empirical Study

Abstract: Does the trio presidency system enhance efficiency in EU legislative decision‐making? Since 2007, fixed groups of three Member States have been required to set a joint 18‐month agenda, with each Member State taking 6‐month turns at the presidency. To date, however, there has been no empirical evidence that either confirms or refutes the notion that this system is efficient. In a study of the duration of Council decision‐making on 1,927 legislative proposals for the 2000–12 period, we obtain empirical support f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 36 publications
0
9
1
Order By: Relevance
“…While the Trio Presidency (and especially the 18-month programme) could be regarded as an additional control, it has generated controversial interpretations in the literature. In his recent study, van Gruisen (2019) shows that the Trio Presidency leads to more efficient decision-making. Having certain proposals pre-negotiated among the Trio members facilitates later negotiations by diminishing political conflict (van Gruisen, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the Trio Presidency (and especially the 18-month programme) could be regarded as an additional control, it has generated controversial interpretations in the literature. In his recent study, van Gruisen (2019) shows that the Trio Presidency leads to more efficient decision-making. Having certain proposals pre-negotiated among the Trio members facilitates later negotiations by diminishing political conflict (van Gruisen, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…In his recent study, van Gruisen (2019) shows that the Trio Presidency leads to more efficient decision-making. Having certain proposals pre-negotiated among the Trio members facilitates later negotiations by diminishing political conflict (van Gruisen, 2019). On the other hand, Trio programmes may be important at the initial stage of cooperation and planning, but have a limited impact on the single Presidency performance (Warntjen, 2013b).…”
Section: Methodsmentioning
confidence: 99%
“…Since we cover 11 years, there were 22 cases of different presidencies. In the Appendix, we also include a dummy for membership in the fixed groups of three member states coordinating their presidency terms and agenda, the well-known trios, introduced in January 2007 (Jensen and Nedergaard 2014;Gruisen 2019).…”
Section: Accounting For Ministers' Participation Ratesmentioning
confidence: 99%
“…Hertz and Leuffen (2011) showed that EU enlargements slowed down decision-making, while Toshkov (2017) questioned this finding. Van Gruisen (2019) demonstrated that the trio presidency format expedites decision-making. By contrast, consultations with external stakeholders prolong negotiations (Rasmussen and Toshkov, 2013).…”
Section: Introductionmentioning
confidence: 99%